Expression of Siglec-1, -3, -5 and -10 in porcine cDC1 and cDC2 subsets from blood, spleen and lymph nodes and functional capabilities of these cells. (August 2020) - Poderoso, T.; De la Riva, P. Martínez; Álvarez, B.; Nieto-Pelegrín, E.; Ezquerra, A.; Domínguez, J.; Revilla, C.
Abstract: Dendritic cells are professional antigen-presenting cells that play a critical role in the development of immune responses. DCs express a variety of Siglecs on their surface, which play a regulatory role modulating their activation through interaction with sialylated structures expressed by cells or pathogens. Here, we characterized the phenotype of porcine conventional dendritic cells subsets from blood, spleen and lymph nodes, emphasizing the analysis of the expression of Siglecs. Siglec-1 was detected in type 1 cDC and, at lower levels, in type 2 cDC in the spleen, being low to negative in blood and lymph node cDC. Siglec-3 and Siglec-5 were expressed in cDC1 at lower levels than in cDC2. Porcine cDCs did not express Siglec-10. cDC2 showed a higher capacity to phagocytose microspheres and to process DQ™-OVA than cDC1, but none of these functions was affected by engagement of Siglec-3 and -5 with antibodies on blood cDC. Highlights: Splenic cDC2 express Siglec-1, being its expression higher on cDC1. cDC2 express higher levels of Siglec-3 and -5 than cDC1. No Siglec-10 expression was found in cDC. cDC2 show a higher ability to phagocytose beads and to process DQ™-OVA than cDC1.